Diversity and origins of Indian multi‐triazole resistant strains of Aspergillus fumigatus. Issue 7 (2nd March 2016) - Chang, Howard; Ashu, Eta; Sharma, Cheshta; Kathuria, Shallu; Chowdhary, Anuradha; Xu, Jianping
Summary: Aspergillus fumigatus is a widespread opportunistic fungal pathogen causing an alarmingly high mortality rate in immunocompromised patients. Nosocomial infections by drug‐resistant A. fumigatus strains are of particular concern, and there is a pressing need to understand the origin, dispersal and long‐term evolution of drug resistance in this organism. The objective of this study was to investigate the diversity and putative origins of triazole resistance of A. fumigatus from India. Eighty‐nine isolates, including 51 multiple triazole resistant (MTR) isolates and 38 azole‐susceptible isolates, were genotyped using multilocus sequence typing (MLST), mating typing and PCR fingerprinting. MLST resolved the 51 MTR isolates into three genotypes, two of which have susceptible counterparts, suggesting that MTR isolates originated multiple times in India. The multiple‐origin hypothesis was further supported by the diversity of sequences at the triazole target gene CYP51A among the MTR isolates, and by PCR fingerprints. Interestingly, there is abundant evidence for mating and recombination in natural population of A. fumigatus in India, suggesting that sexual spread of TR34 /L98H, the dominant MTR allele, is possible. Our results call for greater attention to MTR in A. fumigatus and for better management of antifungal drug use.